A systematic observational study of radio properties of H2O megamaser Seyfert-2 galaxies. Issue 2 (7th December 2016) - Liu, Z. W.; Zhang, J. S.; Henkel, C.; Liu, J.; Müller, P.; Wang, J. Z.; Guo, Q.; Wang, J.; Li, J.
Abstract: A systematic study is performed on radio properties of H2 O megamaser host Seyfert 2 galaxies, through multiband radio continuum observations (at 11, 6.0, 3.6, 2.0 and 1.3 cm) with the Effelsberg 100-m radio telescope within a total time duration of 4 d. For comparison, a control Seyfert 2 galaxy sample without detected maser emission was also observed. Spectral indices were determined for those sources for which measurements exist at two adjacent bands assuming a power-law dependence Sν  ∝ ν −α, where S is the flux density and ν is the frequency. Comparisons of the radio continuum properties between megamaser and non-masing Seyfert 2s show no difference in spectral indices. However, a difference in radio luminosity is statistically significant, i.e. the maser galaxies tend to have higher radio luminosities by a factor of 2–3 than the non-masing ones, commonly reaching values above a critical threshold of 10 29  erg s −1  Hz −1 . This result confirms an earlier conclusion by Zhang et al., but is based on superior data with respect to the time interval within which the data were obtained, with respect to the observational facility (only one telescope used), and the number of frequency bands.